Clinical Spectrum and Treatment Outcomes of Patients with Developmental and/or Epileptic Encephalopathy with Spike-and-Wave Activation in Sleep - Nuri Tchah; Donghwa Yang; Heung Dong Kim; Joon Soo Lee; Se Hee Kim; Hoon-Chul Kang (Korean Child Neurology Society, 2022)
Purpose Developmental and/or epileptic encephalopathy with spike-and-wave activation in sleep (D/EE-SWAS) is a spectrum of conditions characterized by various phenotypes of cognitive, linguistic, and behavioral regression associated with spike-and-wave activation in sleep. We aimed to investigate the phenotypic spectrum and treatment outcomes of pediatric patients with D/EE-SWAS. Methods We retrospectively analyzed the medical records of pediatric patients diagnosed with D/EE-SWAS and treated at Severance Children's Hospital from 2006 to 2022. We extracted information from their medical records on electroencephalography before and after treatment, types of treatment, seizure frequency, and developmental profiles. The primary outcome was reduction of the spike-wave index on electroencephalography after treatment. Results Twenty-one patients with a median age of 5.3 years (interquartile range, 4.1 to 6.6) at diagnosis were included. Ten patients had delayed development. The patients received various anti-seizure medications. Fourteen received long-term, high-dose steroid therapy, 10 were placed on a ketogenic diet, four received intravenous steroid pulse therapy, and one each was treated with intravenous immunoglobulin and cannabidiol. The most effective treatments were steroid therapy and a ketogenic diet, which were also effective in reducing seizures and improving cognition. Side effects during treatment were transient and treatable. Conclusion We described the clinical spectrum of pediatric patients with D/EE-SWAS. Steroid therapy and a ketogenic diet can be considered effective therapeutic options for patients with D/EE SWAS.